Student Organization Funds at A University: Utilization of Descriptive-Correlational Analysis to Determine Factors in Budgeting - Liezle B. Ponce; Melissa C. Battad; Rei-sann V. Sabalo; Hannah Mae T. Saguiyod (Inclusive Society and Sustainability Studies, 2024)
Budgeting guarantees that an organization has enough resources to accomplish its objectives. There are various studies that have been published related to budgeting. The budgeting of student organization funds in university remains an understudied domain; thus, this research seeks to fill this gap by contributing to the existing body of knowledge while elucidating the allocation processes to enhance transparency and accountability. The objective of this study was to determine the factors affecting the budgeting of student organization funds in university in Philippines. The study utilized descriptive-correlational analysis supported by survey data gathered through a total enumeration of 16 student organizations, employing a hybrid (online and offline) data collection, identified a statistically significant and positively correlated linear relationship between financial-related factors and managerial-related factors. The study revealed that student organization officers have strong financial knowledge and skills. High scores in financial skills and budgetary planning escalate the effective management in achieving goals, aligning with functional leadership theory. However, there is a need for better training programs to address gaps, particularly in using budgets as forecasts. The study also found that improving interpersonal skills can enhance financial management, and the relationship between financial and managerial skills is consistently positive across different groups. Aside from a discussion of the findings considering the relevant reviewed literature, there are recommendations to academics and practitioners, as well as proposals for further study in this field. Along with these results, it is best for universities to consider integrating budget-related training and seminars if they want to have well- rounded student leaders who are indeed capable of leading and providing good-quality service to their fellow students.